Influence of ageing on the corrosion behaviour of 2024 aluminium alloy coated with a trivalent chromium conversion layer. (15th April 2021) - Saillard, R.; Zanna, S.; Seyeux, A.; Fori, B.; Światowska, J.; Blanc, C.; Marcus, P.
Graphical abstract: Highlights: Ageing at 190 °C leads to a thicker and Cu(II)/Mg-rich oxide layer on AA2024. Cu enrichment in the oxide and underlying aged AA2024 is induced by pre-treatment. TCP coating structure and chemical composition depend on the Cu enrichment. High Cu coverage is combined with a rougher TCP coating/substrate interface. High Cu coverage leads to more defective coating and low anticorrosive properties. Abstract: Time-of-flight secondary ion mass spectrometry and X-ray photoelectron spectroscopy were used to study the influence of ageing of 2024 aluminium alloy at 190 °C on subsequent degreasing and deoxidation behaviour. After degreasing and deoxidation of the aged alloy, an increase in the surface Cu coverage and a surface roughening were observed as compared to a non-aged alloy. The Cu surface enrichment affected the growth mechanisms of the trivalent chromium process (TCP) coating. The TCP coating formed on an aged sample was thicker, but more defective leading to the decrease of its anticorrosion properties, as compared to a non-aged sample.